CURAHAN TENAGA KERJA PADA USAHATANI PADI DI DESA LOWIAN KECAMATAN MAESAAN - Trifly ., Kawengian; Juliana Ruth Mandey; Nordy Fritsgerald Lucky Waney (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the time allocation of labor in rice farming. The study was conducted in Lowian Village, Maesaan SubDistrict, South Minahasa Regency. Data collection is done by survey method. The number of samples of rice farmers is determined as many as 20 farmers. Determination of the sample is done by simple random sampling. Data analysis was performed descriptively in form of tables and verbal descriptions. The types of paddy farming activities studied include land management activities, nursery seedlings, planting, weeding, fertilizing, eradicating pests and diseases, harvesting, transporting and drying or dry in the sun activities. The average amount of time allocation of labor in one hectare of paddy farming is 136 HOK (Workers' Day). The most labor-intensive activities were planting and harvesting activities, respectively 33.5 HOK (26.4%) and 32.1 HOK (25.1%). The least labor-intensive activity in transportation activities was 3.1 HOK (2.5%) and seedling nursery activities were 4.5 HOK (3.5%). Land management activities 97.15 percent use animal power and 2.85 percent use tractors. Other activities fully use human labor. The amount of time allocation of male laborers was 78.375 HOK (66.56%) and the total flow of female labor was 39.375 HOK (33.44%). The types of activities undertaken by women are seedling activities, planting, weeding and paddy drying or dry in the sun. *eprm*